Hyaline vascular variant of unicentric Castleman disease of the tonsil: a case report - Ping Li; Huaipu Liu; Hao Li; Ang Li; Guangyin Yu; Weihua Yin (BMC, 2019)
Abstract Background Castleman disease (CD) is a lymphoproliferative disorder with an unknown etiology. The disease may be unicentric (UCD) or multicentric (MCD), and three histopathologic variants have been described: hyaline vascular (HV), plasma cell (PC), and mixed type. Extranodal CD is rare. Herein, we report a case of CD presenting as a tonsillar mass, which has not been documented in the literature. Case presentation The patient was a 32-year-old man. Laryngoscopy revealed tonsillar hypertrophy, and the patient underwent a low-temperature plasma tonsillectomy. Microscopic examination of permanent sections showed lymphoid follicular hyperplasia, a portion of which appeared to be a fusion of nodular hyperplasia (composed of lymphoid follicles of variable size and shape). These distinctive follicles with atrophic hyalinized germinal centers and a broad mantle zone of small lymphocytes formed concentric rings (so-called onion-skin arrangement). Medium-sized vessels and a plethora of capillaries were present in the center of the lymphatic follicles, mantle zones, and interfollicular areas. A characteristic lollipop appearance was also observed due to the onion-skin arrangement of the expanded mantle zone lymphocytes with a vessel penetrating the germinal center. No aberrant lymphoid population was present based on CD3, CD5, CD20, CD79α, CD21, CD23, bcl-2, cyclin D1, and ki-67 immunostaining. Tests for human herpesvirus (HHV)-8 and Epstein Barr virus (EBV)-encoded small RNA (EBER) were negative. Therefore, a diagnosis of an HV variant UCD was rendered. The patient was treated by local excision without any other therapy based on the diagnosis. At the 7-month follow up, the patient had no recurrent symptoms or masses. Conclusion We present an unusual case of a tonsil presenting hyaline vascular Castleman disease (HVCD). This study aims to highlight CD as a differential diagnosis that should be considered by otolaryngologists and pathologists for lymphoproliferative disorders of the tonsil.